Less is More - A Critical View of Further EU Action Towards a Harmonized Corporate Governance Framework in the Wake of the Crisis - Shuangge Wen (Washington University Global Studies Law Review, 2013)
Coming in the wake of the current financial crisis, European developments in corporate governance have received intensive attention, especially during a period when the market volatility of the European Union calls its future integrity into question. This paper seeks to contest further action from the European Union level towards establishing “a harmonized corporate governance framework” with reference to both its desirability and practical feasibility. Starting with a critical evaluation of the factors underpinning the legitimacy of integration, which questions the appeal of “more Europe” in the post-crisis context, the paper casts further doubt on the major harmonization methods of corporate governance, initially based on arguments grounded in the real world and then drawing on theoretical conundrums. Practically, it appears more feasible and desirable to aim for an improved variety of governance systems while leaving open the possibility of flexibility and national distinctions between practices.
Keywords: European Union; EU; corporate governance; finance; financial crisis